PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN DOLO BARAT KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Alfons, Megie (Katalogis, 2018)
The study aims to find out and analyze simultaneous and partial influences of work environment, work motivation, and work satisfaction on the perfomance of middle schools teachers in West Dolo District of Sigi Regency, Central Sulawesi. The study involves 43 respondents who selected by census method. Data analysis is quantitative approach running with Statistical Product and Service Solution 18.0 (SPSS0 with multiple linear regressions analysis. The result of the study concludes that: 1) work environment, work motivation, and work satisfaction simultaneously have significant influence on the perfomance of middle schools teachers in West Dolo, Sigi Regency, Central Sulawesi; 2) work environment has significant influence on middle schools teachers’ perfomance in West Dolo, Sigi Regency, Central Sulawesi; 3) work motivation has significant influence on middle schools teachers’ perfomance in West Dolo, Sigi Regency, Central Sulawesi; 4) work satisfaction has significant influence on middle schools teachers’ perfomance in West Dolo, Sigi Regency, Central Sulawesi;